A Study of Copyrolysis Characteristics of Sewage Sludge and Waste Polypropylene. (30th March 2023) - Chen, Guan-Bang; Huang, Kuan-Chieh
Abstract : This study investigates the copyrolysis of sewage sludge (SS) and waste polypropylene (PP). SS exhibited low heating value and high ash content, whereas PP had a high heating value and volatile content. The properties of SS and PP were analyzed, and copyrolysis process, activation energy, synergistic effects, and gas yield were investigated using thermogravimetry combined with Fourier-transform infrared spectroscopy. The results showed the existence of a three-stage synergy, and 10 % PP + 90 % SS showed maximum aromatic yield. The activation energy value for the blended fuel exhibited positive synergy. The Taguchi method was used to determine the operating conditions in a high-temperature furnace for the maximum C5–12 /C19+ ratio and optimal pyrolysis oil quality. The PP : SS ratio was the most influencing parameter, followed by the pyrolysis temperature. 30% PP and 10% PP had the best C5–12 /C19+ ratio and pyrolysis oil quality, respectively. We obtained a maximum C5–12 /C19+ ratio of 9.1 and the optimal ratio of petrochemical product components (alkenes + monoaromatics ) to worthless products (polyaromatics + cyclic compounds ) of 4.02. The optimal experimental parameters to achieve these two targets were operated with 10% HZSM-5 and activated alumina. HZSM-5 improved the heating value, oil yield, carbon-number ratio, and pyrolysis oil quality.